An Information-Theoretical Perspective on Consciousness: Implications for the Treatment of Death Anxiety - Shapiro, Yakov; Maldonado, Carlos E. (Journal of Scientific Exploration, 2026)
In this paper, we propose a trans-materialist information-theoretical approach to a full spectrum of conscious experience, from its normative embodied mode as part of an integrated brain/mind system to altered modes of consciousness, including nonlocal and near-death experiences (NDE). It allows for bridging the Cartesian gap and resolving the “hard problem” of non-material mind arising from material brain. The first part focuses on quantum information science, specifically an extension of the Bohmian model that re-defines brain/mind from a Cartesian duality to a unified quantum/classical system based on implicate informational dynamics that underlie both the physiological processes of the brain and phenomenological processes of the mind. In this light, consciousness, personal identity and free will are seen as informational processes that incorporate both classical matter/energy and quantum field domains. We then review reports of veridical information obtained during near-death experiences (NDEs), which support the view of consciousness and self-identity as coherent informational patterns (CIPs) that may persist in the absence of a functioning brain. The second part will focus on using the informational framework as a clinical tool in alleviating the ubiquitous experience of existential death anxiety.